(untitled) (Praxis Educativa, 2012)
This paper concerns a research project under development in ‘Teacher Training’, subject belonging to Educational Sciences of the School of Humanities and Art, Rosario National University, and its main purpose is to connect the university with local institutions. In the hermeneutical, reflexive and critical theories, practice is considered as a process in which ways of conceiving it are internalised, sometimes acritically. It is therefore essential in systematic training to work in such a way that allows for the critical revision of the professional ‘habitus’ that is being developed. Learning systematic reflection and practice socialization is necessary during the training process and it allows for a constructive process based on professional knowledge. Besides, some means are analysed to be used to that end: narration, socialization in workshops, working in pedagogical pairs, research projects articulated with local institutions and co-training teachers, and the use of research instruments.